AKIBAT HUKUM DEBITUR WANPRESTASI ATAS PERMOHONAN PELAKSANAAN EKSEKUSI OBJEK JAMINAN FIDUSIA - NIM. A1011181129, MUHAMMAD RIDHO HENDRAWAN KUSUMA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac Fiduciary security is a security right over movable objects as collateral for repayment of certain debts. Executing fiduciary guarantees is one way that can be done to minimize the amount of uncollectible financing. However, this action is currently a controversy and debate among society in Indonesia. There are pros and cons in implementing the execution of fiduciary guarantees in society, especially during a pandemic like the current one and in addition there is a multi-interpretive understanding of Constitutional Court (MK) Decision Number 18 /PUU-XVII/2019 related to the Review of Law Number 42 of 1999 concerning Fiduciary Guarantees both from the public, financing business players and legal practitioners.As for the problem in this research, seen from the description in the background above, the author draws the following conclusions: